Primary malignant melanoma of the parotid gland, a rare case arising from a duct: a case report and literature review - Aung, Moe Thu Zar; Kim, Jo-Eun; Yoon, Hye-Jung; Huh, Kyoung-Hoe; Yi, Won-Jin; Heo, Min-Suk; Lee, Sam-Sun (Frontiers in Oncology, 2024)
Malignant melanoma of the parotid gland is an unusual tumor in the head and neck region, and most parotid melanoma is reported as a metastatic lesion of cutaneous malignant melanoma. We report a case of primary malignant melanoma arising in the parotid gland duct with diagnostic challenge. The patient was a 68-year-old male who complained of repeated right facial swelling that presented three months prior. Swelling was detected along the Stensen's duct of the cheek, and brown-colored saliva-like fluid was aspirated. On MR and CT images, a fluid-filled duct with small nodule and heterogeneously enhancing mass in the parotid parenchyma were detected. The nodular mass on the ductal wall grew rapidly, and the hyperintense T1 signal became significant on follow-up images. The final diagnosis via histopathologic examination using biopsy and parotidectomy specimen revealed the lesion as malignant melanoma of the duct and pleomorphic adenoma of the parenchyma. Even if the incidence of primary malignant melanoma is very low among tumors occurring in the parotid gland, efforts supporting an early diagnosis using imaging characteristics are important.